Infection Pattern of PVY and PLRV in Potato Tubers Obtained from Potato Plants Infected with Both the Viruses (The Agriculturists, 2010)
Experiments were conducted to study the plant growth and tuber yield of the seed potato collected from PVY and PLRV infected plants. The seed potatoes were graded as under size (55 mm) which were planted following RCBD in the field. Third generation seed potatoes of Diamant variety were used. The incidence of viruses was confirmed by DAS-ELISA. The incidence of PVY and PLRV was 100% in the plants raised from under size tubers. The lowest plant height, stem number/hill, tuber weight /hill was recorded in plants raised from under size tuber. It was observed that some of the plants raised from tubers A grade, B grade and oversize tubers remained virus free even when the tubers were collected from virus infected plants.